Health as a Social Issue: a Narrative of Service Amidst Unequal Access to Medical Services - Hutapea, Lyna M. N.; Hutapea, Dwight Mahaputera Marulitua (Oshada, 2025)
Health is understood as a universal basic right that is inseparable from human existence and requires state guarantees through fair and equitable access to services. Fulfillment of this right is not only related to the availability of medical facilities, but also to ensuring equal access without discrimination based on social, economic, or geographic status. The phenomenon of health service inequality in Indonesia shows the concentration of modern facilities in urban areas, while communities in rural and remote areas face structural barriers, including limited infrastructure, medical personnel, and funding. This condition not only increases morbidity and mortality but also reinforces social exclusion rooted in the unfair distribution of resources. On the other hand, narratives of the dedication of health workers in marginalized areas demonstrate dedication that transcends material limitations and becomes a form of social solidarity in fighting for the public's right to health. These narratives simultaneously critique the unequal distribution of health care systems and inspire the integration of empathy and compassion into medical services. This research uses a qualitative approach through a literature review, examining academic journals, policy documents, and international reports to identify key themes related to inequality in access and the social dimensions of health. The analysis was conducted using content analysis to reduce data, categorize issues, and synthesize relevant narratives to obtain a comprehensive picture of the links between health, social justice, and sustainable development. The study's findings confirm that health should be viewed as a strategic investment and a pillar of social justice, requiring data-driven policies, proportional resource distribution, and active community participation. Therefore, equitable fulfillment of the right to health is a crucial foundation for building a more equal, inclusive, and competitive nation